Two new species of Commoneria Horak & Komai, 2006 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Pinkaew, Nantasak; Muadsub, Sopita; Jaikla, Soraya (Zootaxa, 2022)
The genus Commoneria is recorded for the first time from Thailand, represented by two new species: Commoneria sinuata sp. nov. and Commoneria costaplica sp. nov. Illustrations of adults and genitalia are provided. The new taxa increase the number of described Commoneria species to three worldwide.